2019
DOI: 10.3390/pharmacy7030124
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside Allergic Reactions

Abstract: Aminoglycosides are antimicrobial agents that are primarily used for infections caused by Gram-negative pathogens. The purpose of this article is to review the allergic reactions reported in the published literature to aminoglycoside antibiotics. A thorough PubMed search was conducted and excluded non-allergic adverse reactions to aminoglycosides. Allergic reactions to aminoglycosides occur infrequently, but can include cutaneous reactions as well as systemic reactions, including anaphylaxis. Of the evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…In our patients, however, the main reason for revision surgery was contact allergy to gentamicin sulfate, as con rmed by positive patch testing. Aminoglycoside antibiotics are well studied contact allergens, [55] known to be responsible for contact dermatitis to topical drugs in particular, with gentamicin sulfate leading the way. [56] In line with this, a longitudinal study of 620 Finnish patients with suspected contact allergy revealed a 4.6% prevalence of positive patch test reactions to gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…In our patients, however, the main reason for revision surgery was contact allergy to gentamicin sulfate, as con rmed by positive patch testing. Aminoglycoside antibiotics are well studied contact allergens, [55] known to be responsible for contact dermatitis to topical drugs in particular, with gentamicin sulfate leading the way. [56] In line with this, a longitudinal study of 620 Finnish patients with suspected contact allergy revealed a 4.6% prevalence of positive patch test reactions to gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…In our patients, however, the main reason for revision surgery was contact allergy to gentamicin sulfate, as confirmed by positive patch testing. Aminoglycoside antibiotics are well studied contact allergens [ 55 ], known to be responsible for contact dermatitis to topical drugs in particular, with gentamicin sulfate leading the way [ 56 ]. In line with this, a longitudinal study of 620 Finnish patients with suspected contact allergy revealed a 4.6% prevalence of positive patch test reactions to gentamicin [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our patients, however, the main reason for revision surgery was contact allergy to gentamicin sulfate, as confirmed by positive patch testing. Aminoglycoside antibiotics are well studied contact allergens, [49] known to be responsible for contact dermatitis to topical drugs in particular, with gentamicin sulfate leading the way. [50] In line with this, a longitudinal study of 620 Finnish patients 9 with suspected contact allergy revealed a 4.6% prevalence of positive patch test reactions to gentamicin.…”
Section: Discussionmentioning
confidence: 99%